1990
DOI: 10.1007/bf02051919
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between blood plasma prostaglandin E2 and liver and lung metastases in colorectal cancer

Abstract: The relationship of prostaglandin E2, of which a large amount is produced in various neoplasms, and hematogenous distant metastases was investigated in a total of 44 colorectal cancer patients because of its varied pathophysiologic potentials. The authors found significantly high levels of PGE2 in local venous blood draining the carcinoma and in peripheral blood in cases with liver or lung metastasis, as well as a significantly large amount of PGE2 production in the carcinoma tissue. The results suggest that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…38 Levels of PGE 2 and Tregs in the peripheral blood also may reflect the biology of the disease and motivate the use of an anti-COX-2 and anti-Treg therapy. 39,40 To develop novel therapeutic strategies, we must gain insight into the mechanisms of Treg control and regulation in UM.…”
Section: Discussionmentioning
confidence: 99%
“…38 Levels of PGE 2 and Tregs in the peripheral blood also may reflect the biology of the disease and motivate the use of an anti-COX-2 and anti-Treg therapy. 39,40 To develop novel therapeutic strategies, we must gain insight into the mechanisms of Treg control and regulation in UM.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] It has been reported that there was a correlation between an increased PGE 2 concentration and the risk of cancer development. [28][29][30][31] On the other hand, PGE 1 converted from DGLA has anti-inflammatory [32][33][34] and anti-platelet aggregation activities. 4) It has been indicated that DGLA and PGE 1 inhibited the synthesis of pro-inflammatory mediators such as LTB 4 , LTC 4 , and LTD 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Although NSAIDs inhibit cyclooxygenase which catalyses the biosynthesis of PGH 2 , precursors for prostanoids such as prostaglandins, the mechanisms by which inhibition of PG synthesis contribute to decreased carcinogenesis in colon and some other tissues have yet to be defined. In addition to breast cancer, studies have shown that colon cancer tissues produce a large amount of PGE 2 (Narisawa et al, 1990). Moreover, our very recent study showed that a potent stimulatory effect of IL-1 on HGF production in fibroblasts was mediated via PGE 2 production and was almost completely abrogated by indomethacin (unpublished data).…”
Section: Discussionmentioning
confidence: 73%